Temperature‐Sensitive Magnetic Drug Carriers for Concurrent Gemcitabine Chemohyperthermia. Issue 5 (21st October 2013) - Kim, Dong‐Hyun; Guo, Yang; Zhang, Zhuoli; Procissi, Daniel; Nicolai, Jodi; Omary, Reed A.; Larson, Andrew C.
<x xml:space="preserve">Abstract</x> To improve the efficacy of gemcitabine (GEM) for the treatment of advanced pancreatic cancer via local hyperthermia potentiated via a multi‐functional nanoplatform permitting both in vivo heating and drug delivery is the goal of this study. Here, a chemohyperthermia approach to synergistically achieve high intra‐tumoral drug concentrations, while permitting concurrent hyperthermia for more effective tumor cell kill and growth inhibition, is proposed. Drug delivery and hyperthermia are achieved using a hydroxypropyl cellulose (HPC)‐grafted porous magnetic drug carrier that is MRI visible to permit in vivo visualization of the biodistribution. These synthesized magnetic drug carriers produce strong T2‐weighted image contrast and permit efficient heating using low‐magnetic‐field intensities. The thermomechanical response of HPC permits triggered GEM release confirmed during in vitro drug release studies. During in vitro studies, pancreatic cancer cell growth is significantly inhibited (≈82% reduction) with chemohyperthermia compared to chemotherapy or hyperthermia alone. Using PANC‐1 xenografts in nude mice, the delivery of injected GEM‐loaded magnetic carriers (GEM‐magnetic carriers) is visualized with both MRI and fluorescent imaging techniques. Chemohyperthermia with intra‐tumoral injections of GEM‐magnetic carriers (followed by heating) results in significant increases in apoptotic cell death compared to tumors treated with GEM‐magnetic carriers injections alone. Chemohyperthermia with GEM‐magnetic carriers offers the potential to significantly improve the therapeutic efficacy of GEM for the treatment of pancreatic cancer. In vivo delivery confirmation with non‐invasive imaging techniques could permit patient‐specific adjustments therapeutic regimens for improve longitudinal outcomes.